Impact of health, husbandry, and conservation research on glucocorticoid concentrations in Atelopus species - Cikanek, Shawna (Kansas State University, 2013)
In many species, temporary increases in glucocorticoids (GC) can be used to identify changes in adrenal activity in response to acute stressors. For this research, GC metabolites were identified in fecal extracts from various Atelopus species. The objectives were to identify possible correlates between GCs and health status, assess the impact of husbandry protocols on adrenal activity, and evaluate the sub-lethal effects of antifungal bacteria used for protection of frogs against the chytrid fungus (Batrachochytrium dendrobatidis; Bd). The first study examined whether fecal GC concentrations can be correlated with animal health and behavior changes in a captive setting. Atelopus zeteki with varying degrees of dermatitis were categorized based on the severity of their skin abnormalities and GC metabolite concentrations were analyzed to detect correlations between severity of disease and GC metabolite concentrations. Similarly, behaviors that may indicate elevated stress levels (e.g., time spent in hide) were analyzed to detect correlation between disease and behavior changes. There was no correlation between fecal GC metabolites and health status of the animal or between health status and amount of time spent in hide. The second study established ex situ colonies of two Panamanian frog species, Atelopus certus and Atelopus glyphus, to determine how male group size affects behavior and GC levels. When housed in groups of eight, animals initially had elevated GC concentrations and interacted aggressively, but these instances declined substantially in the first 2 weeks of being housed together. Thus, captive Atelopus populations can be housed in same-sex enclosures without causing sub-lethal stress on the individuals involved. The third study examined the ability of antifungal bacterium from Central America to propagate on Atelopus skin as a preventative treatment for Bd and the sub-lethal effects of each bacteria species on adrenal function based on GC analysis. Four species of bacteria (Pseudomonas sp., Pseudomonas putida, Chryseobacterium indolgenes, and Stenotrophomonas maltophili) were found to be successful Bd inhibitors in vitro. There were no detectable effects of bacterial exposure with GC metabolite concentrations over time for any of the treatments assessed.
Keywords: Batrachochytrium dendrobatidis; Chytridiomycosis; Atelopus; Glucocorticoids; Cortisol; Wildlife Conservation (0284); Wildlife Management (0286)